2021
DOI: 10.3390/horticulturae7110421
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Ripening on Polyphenolic Content, Degradative, and Browning Enzymes in Cantaloupe Varieties (C. Melo, L.)

Abstract: The biochemical changes that occur during the growth and ripening of fruit and vegetable tissues, especially for color and firmness, are the most important factors affecting the quality of fresh products. Cantaloupe (Cucumis melo, L.) is one of the main economically important fruits in the world and its quality parameters, e.g., sweetness, nutritional factors, and texture, influence consumer preferences. Hence, these two features, appearance and texture changes, were investigated in three different genotypes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…During fruit softening, the changes of cell wall materials mainly stemmed from the variation in the cell wall modifying enzyme activities. PG, Cx, PME, XTH, α-ARF, and β-GAL were cell-wall-degrading enzymes involved in fruit softening [ 2 , 3 , 36 , 37 ]. The activities concerning Cx, PG, α-ARF, or β-GAL regularly multiplied with the development of storage time.…”
Section: Resultsmentioning
confidence: 99%
“…During fruit softening, the changes of cell wall materials mainly stemmed from the variation in the cell wall modifying enzyme activities. PG, Cx, PME, XTH, α-ARF, and β-GAL were cell-wall-degrading enzymes involved in fruit softening [ 2 , 3 , 36 , 37 ]. The activities concerning Cx, PG, α-ARF, or β-GAL regularly multiplied with the development of storage time.…”
Section: Resultsmentioning
confidence: 99%
“…reticulatus Naudin) from 38 days after anthesis to overripe. Furthermore, [38] reported that there was an increase in TSS content in 3 cultivars of cantaloupe melon from the unripe stage to the overripe stage.…”
Section: Content Of Vitamin a Vitamin C And Tss At Five Maturity Stagesmentioning
confidence: 99%
“…Reduced luminosity observed in uncoated melons may be associated with polyphenol oxidase activation, which causes enzymatic browning due to physiological damage. In contrast, the coated samples showed reduced browning due to reduced oxygen penetration, reducing oxidation rates [ 77 ]. Moreover, the probiotic-loaded edible coating or coatings prevent the enzymatic oxidation of phenolic compounds, thereby protecting them [ 71 ].…”
Section: Resultsmentioning
confidence: 99%